Evaluation of Hemoptysis in Patients With a Normal Chest Roentgenogram - Peters, Jay (1984)
Hemoptysis is a common presenting complaint in patients with pulmonary disease. Although controversial, many clinicians suggest that all patients with hemoptysis should be evaluated with bronchoscopy to exclude the presence of a serious pathologic condition. We reviewed records for an 18-month period, during which 113 patients had hemoptysis as their principal complaint. In all, 26 of the 113 patients had normal chest roentgenograms. All underwent bronchoscopy as part of their evaluations. Results of bronchoscopy in these patients neither altered therapeutic decisions nor led to diagnoses of specific pathologic processes. We conclude that close observation of patients with normal chest roentgenograms who have hemoptysis may be an acceptable clinical approach.